Role of the cutaneous extraneuronal cholinergic system in the pathogenesis of psoriasis: a case–control study. (1st June 2020) - Abu Zeid, O.; Abdel‐Aziz, A.; Rashed, L. A.; Said, E. R.
Summary: Background: Although during recent years there have been considerable advances in elucidating the mechanisms of psoriasis pathogenesis, its full understanding is still distant. A cholinergic dysfunction has been proposed in the pathophysiology of some inflammatory and autoimmune diseases, including psoriasis. Aim: To determine tissue levels of acetylcholine (ACh) and its muscarinic and nicotinic receptors (mAChR and nAChR) in psoriasis vulgaris lesions in comparison with normal control skin. Methods: This case–control study included 30 patients with psoriasis vulgaris and 30 controls. A 4‐mm punch skin biopsy was taken from the psoriatic plaques of patients and normal skin of controls. ACh level was measured in tissues using the colorimetric method, while mAChR and nAChR gene expression was determined by real‐time PCR. Results: The level of ACh was significantly higher in patients (mean ± SD: 5.95 ± 2.69) than in controls (1.12 ± 0.34) ( P < 0.001). mAChR and nAChR expressions were significantly higher in patients compared with the controls ( P < 0.001). A significant positive correlation was detected between the expression of nAChR in patients and the duration of psoriasis ( r = 0.46, P = 0.01), and the body mass index of the patients correlated positively with both nAChR ( r = 0.40, P = 0.027) and mAChR expression ( r = 0.448, P = 0.013). Conclusion: Abnormalities in the cutaneous extraneuronal cholinergic system could be involved in the pathogenesis of psoriasis. The high expression of nAChRs in patients with longer disease durations might represent an attempt by the body to regulate the inflammatory cascade in psoriatic lesions. The high expression of mAChR in psoriatic lesions may provide a link between psoriasis and obesity.